The Effectiveness of Law Enforcement for Criminal Fraud via WhatsApp in the Legal Area of the Pasangkayu Police - Harapansyah, Mohamad; Rahman, Sufirman; Badaru, Badaruddin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Fraud through WhatsApp has become one of the most frequently reported forms of cybercrime. The modus operandi used by the perpetrators is very diverse, ranging from offering goods or services at low prices but not in accordance with reality, asking for money on behalf of the victim's friends or family, to utilizing the victim's personal data for illegal purposes. Not a few people who are victims of this fraud have experienced significant financial losses, even up to billions of rupiah. Fraud through WhatsApp in Indonesia has become an increasingly worrying problem because according to data from the Indonesian Internet Service Providers Association (APJII) in 2024 states that online fraud is the highest type of cybercrime, reaching 32.5% of total reported cases. This research is a type of empirical legal research oriented to primary legal materials (the results of field research) and the research was conducted at the Pasangkayu Resort Police on the grounds that the selection of the location of the research was based on the consideration that based on the existing facts there were several significant cases in recent years. Law enforcement of fraud crimes through WhatsApp in the jurisdiction of the Pasangkayu Resort Police has not been carried out effectively because in its implementation there are still many unresolved police reports and public complaints that are not followed up due to several things, namely due to policy inconsistency, complexity of reporting and the speed of handling cases is still very low. The lack of effective law enforcement in handling fraud crimes through WhatsApp in the Pasangkayu Resort Police Jurisdiction is due to various factors, namely legal factors, law enforcement factors, facilities and infrastructure factors, community factors and cultural factors.